دور حمدان بن عثمان خوجة في الدفاع عن مصالح الجزائريين بين ( 1830-1833م ) - زهية بولرواح; د/ فاطمة دجاج (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: تهدف هذه الدراسة الى التعريف بقامة من قامات النضال السياسي في بداية الاحتلال الفرنسي للجزائر، ألا وهو حمدان بن عثمان خوجة هذا الذي يعتبر أول رائد للحركة الوطنية الجزائرية على حد قول شيخ المؤرخين "أبو القاسم سعد الله"، وفي هذه الدراسة تم تسليط الضوء على دور حمدان بن عثمان خوجة في الدفاع عن مصالح الجزائريين ما بين 1830الى1833م، من خلال مساعيه لجعل الفرنسيين يلتزمون بما جاء في معاهدة الاستسلام وحق الجزائريين في تقرير مصيرهم وتجلى نشاطه السياسي في العرائض والشكاوي التي كان يرسلها الى الجهات الرسمية الفرنسية والعثمانية وقد عمل جاهدا على الدفاع عن القضية الجزائرية داخل الجزائر وخارجها. الكلمات المفتاحية : حمدان بن عثمان خوجة ، الدفاع ، مصالح الجزائريين. Study Summary: This study aims to introduce the stature of the political struggle at the beginning of the French occupation of Algeria, namely Hamdan bin Othman Khoja, who is considered the first pioneer of the Algerian national movement, according to the Sheikh of historians, "Abu al-QasimSaad Allah", and in this study was highlighted the role of Hamdan bin Othman Khoja in defending the interests of Algerians between 1830 to 1833 AD, through his efforts to make the French abide by what was stated in the surrender treaty and the right of Algerians to self-determination His political activity was evident in the petitions and complaints he sent to the French and Ottoman official bodies, and he worked hard to defend the Algerian cause inside and outside Algeria. Keywords:Hamdan Ben Othman Khoja, defense, interests of Algerians.